Shariah governance for Islamic banking: What can be learnt from Malaysia? - Rifqi Muhammad (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Islamic financial institutions have unique characteristics that avoid interest-based transaction and operate in accordance with Shariah principles. Therefore, the governance mechanism is also different with conventional institutions. One of important component in the governance structure in Islamic financial institution is the existence Shariah Supervisory Board (SSB). Shariah govenrnance is the governance mechanism in Islamic financial institutions that involves the position of SSB as the guard of shariah compliance process. This paper is mainly discusses the implementation of Shariah govenrnance practices by Islamic banks in Malaysia. Malaysia is one of the countries that seriously develops Islamic banking governance structure and Shariah govenrnance mechanism. Thus, this paper will discuss several issues as follows: Firstly, the nature of Shariah governance and the roles of SSB members. Secondly, the Shariah Governance Framework in Malaysia. Thirdly, the practices of Shariah governance and auditing in Malaysia. Finally, this paper attempts to evaluate the Shariah governance practices by Islamic banks in Malaysia and describes some aspects that can be learnt from Malaysia.